BIOSAFETY: A MULTIDISCIPLINARY APPROACH IN CONTRIBUTION TO ENVIRONMENTAL EDUCATION - Bohner, Tanny Oliveira Lima; Bohner, Lauren Oliveira Lima; Cassol, Paulo Barrozo; Pessoa, Ana Carolina Monteiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This study presents a reflective character on biosafety, with its implications and responsibilities ofprofessionals who use it in their work processes. Thus, in order to accomplish an interdisciplinaryactivity in contribution to environmental education, each professional described the importance ofusing PPE within their field. The forest engeneer is going to address the biosafety regardingprotection during agricultural production. The dentist is going to discuss the same topic, from ahealth and safety perspective on the treatment of patients. On the other hand, the nurse willbound its importance on the health care. And the vet is going to focus on the necessary protection This study presents a reflective character on biosafety, with its implications and responsibilities ofprofessionals who use it in their work processes. Thus, in order to accomplish an interdisciplinaryactivity in contribution to environmental education, each professional described the importance ofusing PPE within their field. The forest engeneer is going to address the biosafety regardingprotection during agricultural production. The dentist is going to discuss the same topic, from ahealth and safety perspective on the treatment of patients. On the other hand, the nurse willbound its importance on the health care. And the vet is going to focus on the necessary protection